2014
DOI: 10.1038/nature13731
|View full text |Cite
|
Sign up to set email alerts
|

Global covariation of carbon turnover times with climate in terrestrial ecosystems

Abstract: The response of the terrestrial carbon cycle to climate change is among the largest uncertainties affecting future climate change projections. The feedback between the terrestrial carbon cycle and climate is partly determined by changes in the turnover time of carbon in land ecosystems, which in turn is an ecosystem property that emerges from the interplay between climate, soil and vegetation type. Here we present a global, spatially explicit and observation-based assessment of whole-ecosystem carbon turnover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
759
5
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 756 publications
(823 citation statements)
references
References 59 publications
(53 reference statements)
58
759
5
1
Order By: Relevance
“…However, they were similar to the results from a nearby Kobresia meadow in Xinghai (Hafner et al, 2012), where values of 4.2 and 5.5 days were reported for grazed and ungrazed grasslands, respectively. The results suggest differences in grassland types and climate (i.e., alpine steppe in the present study vs. alpine meadow in previous studies) attributable to a clear dependence of the TR on temperature (Carvalhais et al, 2014).…”
Section: Grain For Greensupporting
confidence: 42%
See 3 more Smart Citations
“…However, they were similar to the results from a nearby Kobresia meadow in Xinghai (Hafner et al, 2012), where values of 4.2 and 5.5 days were reported for grazed and ungrazed grasslands, respectively. The results suggest differences in grassland types and climate (i.e., alpine steppe in the present study vs. alpine meadow in previous studies) attributable to a clear dependence of the TR on temperature (Carvalhais et al, 2014).…”
Section: Grain For Greensupporting
confidence: 42%
“…In terrestrial ecosystems, the size of the C reservoir for the whole ecosystem equals the C stocks in the vegetation and soil (Carvalhais et al, 2014), and is an ecosystem property that indicates C sequestration capability of an ecosystem (Zhao et al, 2015). This was represented by the C stocks in the shoots, roots, and soil in the present study.…”
Section: Grain For Greenmentioning
confidence: 80%
See 2 more Smart Citations
“…Among the treatment factors, temperature had the strongest effect on the temporal dynamics of soil C mineralization; a decrease in the incubation temperature from 25 to 5°C resulted in a delayed peak and reduced magnitude of the maximum rate of C mineralization during the study period. This is consistent with previous findings that climate exerts dominant controls on SOM decomposition (Carvalhais et al., 2014; Kirschbaum, 2004; Sun et al., 2004). A recent synthesis by Luo, Feng, Luo, Baldock, and Wang (2017) showed that climate (precipitation and temperature) accounted for as much as 25% of the relative influence on SOC by various environmental, soil biotic, and abiotic factors.…”
Section: Discussionmentioning
confidence: 99%